STUDI POTENSI PEMBANGKIT LISTRIK TENAGA PIKO HIDRO DI ALIRAN SUNGAI IRIGASI SUBAK WERDI PUTRA SEDANA KABUPATEN BADUNG - Ida Bagus Gede Wira Negara; I Gusti Ngurah Janardana; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2022)
In addition to solar and wind energy, the hydrological cycle can be used for energysources by utilizing waves or currents or water potential e nergy due to differences in water level.This water energy is energy that has not been utilized optimally. In general, the utilization of thisenergy source is carried out on a large scale and requires very large costs. According toobservations, the Dukuh Moncos Traditional Village has the potential for generating electricitybecause the river flows are quite stable and sustainable. In this study, a study was conductedon the potential of the Werdi Putra Sedana irrigation river flow around the Kelaci Templ e, DukuhMoncos Traditional Village, Sobangan Village, Mengwi District, Badung Regency to be utilizedas a pico hydro power plant with quantitative and descriptive methods. This study was carriedout by measuring the water flow rate then measuring the head or height difference then continuously measuring the hydraulic potential, from the measurement stage and obtaining theresults then calculating the potential power generated by the irrigation river so that the powergenerated was obtained. The flow of the Werdi Putra Sedana subak river in Banjar HamletMoncos, Sobangan Village, Mengwi District, Badung Regency has the potential to be used asan alternative energy source, namely a pico hydro power plant (PLTPH) with an average powerof 3.86 kW.